Zum langfristigen Abflußverhalten und seinen Steuerungsmechanismen im periglazialen Zentral-Island - Richter, Klaus (ERDKUNDE, 1982)
The existence of long-term hydrological raw data material for Icelandic rivers offers the rare opportunity of identifying the hydrological conditions of glacial-periglacial river basins quantitatively and of analysing them as to the variability of these conditions. The present paper deals with the long-term runoff behaviour (1940-1979) of the Jokulsa a Fjollum river basin (7180 km2) in the north-eastern part of the Icelandic highlands.22% of the area which receive 47% of the area precipitation are glaciated by a part of the Vatnajokull ice-cap.79% of the long-term water input supply the runoff, 21% evaporate. A seasonal and regional subdivision of the river basin reveals that the runoff is composed of, first, a relatively high base flow as a result of the permeable volcanic rocks and the unconsolidated sediments in the research area, of, secondly, snow meltwater from the unglaciated area as a result of increasing energy input in spring, and of, thirdly, glacial meltwater from the glaciated area as a result of relatively high summer energy input. For the river basin taken as a hydrological unit, direct glacial ablation runoff and the long term infiltration of rain, of snow meltwater, and, most important, of glacial ablation water into the ground are, in connection with a northbound groundwater flow, the determining factors of the amount of the annual runoff. Correlation and regression analyses support these findings. Accordingly, the thermic-climatic development of the past forty years is reflected in the long-term runoff behaviour and results in considerable variations of the mean discharge during this period.